THE EFFECT OF CONTENT MARKETING AND BRAND IMAGE ON PURCHASE INTENTION OF SPECS PRODUCTS ON TIKTOK SHOP - Dimas Satria Ramandha; Ika Diyah Candra Arifah; Hafid Kholidi Hadi; Muhammad Fachmi (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the influence of Content Marketing and Brand Image on Purchase Intention toward Specs products on TikTok Shop. The research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 as the analytical tool. Data were collected through an online questionnaire distributed to 125 respondents who are active TikTok users and have purchased Specs products through TikTok Shop within the last six months. The findings reveal that Content Marketing has a positive and significant effect on Purchase Intention, indicating that engaging, informative, and value-driven content can effectively encourage consumers’ buying interest. In addition, Brand Image also demonstrates a positive and significant influence on Purchase Intention and emerges as the more dominant factor in shaping consumer intention. The coefficient of determination (R²) value of 0.613 indicates that Content Marketing and Brand Image jointly explain 61.3% of the variance in Purchase Intention. These findings highlight the importance of integrating effective digital content strategies with strong brand image development to strengthen consumer purchase intention in the social commerce environment of TikTok Shop. Keywords: Content Marketing; Brand Image; Purchase Intention; TikTok Shop